Saffron extract attenuates neuroinflammation in rmTBI mouse model by suppressing NLRP3 inflammasome activation via SIRT1 - Shaheen, Mariam J.; Bekdash, Amira M.; Itani, Hana A.; Borjac, Jamilah M. (PLOS ONE, 2021)
Traumatic brain injury (TBI) remains a major cause of morbidity and disability worldwide and a healthcare burden. TBI is an important risk factor for neurodegenerative diseases hallmarked by exacerbated neuroinflammation. Neuroinflammation in the cerebral cortex plays a critical role in secondary injury progression following TBI. The NOD-like receptors (NLR) family pyrin domain containing 3 (NLRP3) inflammasome is a key player in initiating the inflammatory response in various central nervous system disorders entailing TBI. This current study aims to investigate the role of NLRP3 in repetitive mild traumatic brain injury (rmTBI) and identify the potential neuroprotective effect of saffron extract in regulating the NLRP3 inflammasome. 24 hours following the final injury, rmTBI causes an upregulation in mRNA levels of NLRP3, caspase-1, the apoptosis-associated speck-like protein containing a CARD (ASC), nuclear factor kappa B (NF-κB), interleukin-1Beta (IL-1β), interleukin 18 (IL-18), nuclear factor erythroid 2–related factor 2 (NRF2) and heme oxygenase 1 (HMOX1). Protein levels of NLRP3, sirtuin 1 (SIRT1), glial fibrillary acidic protein (GFAP), ionized calcium-binding adaptor molecule 1 (Iba1), and neuronal nuclei (Neu N) also increased after rmTBI. Administration of saffron alleviated the degree of TBI, as evidenced by reducing the neuronal damage, astrocyte, and microglial activation. Pretreatment with saffron inhibited the activation of NLRP3, caspase-1, and ASC concurrent to reduced production of the inflammatory cytokines IL-1β and IL-18. Additionally, saffron extract enhanced SIRT1 expression, NRF2, and HMOX1 upregulation. These results suggest that NLRP3 inflammasome activation and the subsequent inflammatory response in the mice cortex are involved in the process of rmTBI. Saffron blocked the inflammatory response and relieved TBI by activating detoxifying genes and inhibiting NLRP3 activation. The effect of saffron on the NLRP3 inflammasome may be SIRT1 and NF-κB dependent in the rmTBI model. Thus, brain injury biomarkers will help in identifying a potential therapeutic target in treating TBI-induced neurodegenerative diseases.